2015
DOI: 10.1002/ijch.201400172
|View full text |Cite
|
Sign up to set email alerts
|

Functional Peptide Monolayers at Interfaces

Abstract: Amphiphilic peptides can be designed to form ordered supramolecular structures at hydrophilic‐hydrophobic interfaces. These systems rely on the ability of peptides to fold into certain secondary structures at interfaces. This review focuses on the design of amphiphilic β‐sheet peptide assemblies in monolayers at interfaces, and their relevance to inducing mineralization and interactions with specific ions. In addition, the review discusses recent studies demonstrating the applicability of designed amphiphilic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Rapaport et al have reviewed the design and application of AP assemblies in monolayers at interfaces. 111 They also reported that acidic b-sheet peptides exhibited compressibility and elasticity, which may be associated with favorable cross-strand interactions between the side chains of peptides. 112 Recently, Bai and Ulijn et al successfully utilized nanofibrous interfacial networks assembled by amphiphilic peptides through p-stacking and hydrogen bonding interactions, to obtain a stable emulsion (Fig.…”
Section: The Kinetic Control Of Ap Self-assemblymentioning
confidence: 98%
“…Rapaport et al have reviewed the design and application of AP assemblies in monolayers at interfaces. 111 They also reported that acidic b-sheet peptides exhibited compressibility and elasticity, which may be associated with favorable cross-strand interactions between the side chains of peptides. 112 Recently, Bai and Ulijn et al successfully utilized nanofibrous interfacial networks assembled by amphiphilic peptides through p-stacking and hydrogen bonding interactions, to obtain a stable emulsion (Fig.…”
Section: The Kinetic Control Of Ap Self-assemblymentioning
confidence: 98%
“…Self-assembling peptides have been identified as candidates that can serve as building blocks in the fabrication of molecular devices: potential applications based on their ease of synthesis, ease and range of accessible chemical modification, and geometrical precision have been discussed in a number of reviews. Recently, for example, advances have been made in the exploration of self-assembling peptides for applications such as drug delivery, organic semiconductor devices, and sensing . There has been significant progress in creating functional supramolecular structures using the Langmuir–Blodgett (LB) technique.…”
Section: Introductionmentioning
confidence: 99%